Inband-pumped, high-power thulium-doped fiber amplifiers for an ultrafast pulsed operation - Lenski, Mathias; Heuermann, Tobias; Gebhardt, Martin; Wang, Ziyao; Gaida, Christian; Jauregui, Cesar; Limpert, Jens (Optics Express, 2022)
We investigate the influence of the pump wavelength on the high-power amplification of large-mode area, thulium-doped fibers which are suitable for an ultrashort pulsed operation in the 2 µm wavelength region. By pumping a standard, commercially available photonic crystal fiber in an amplifier configuration at 1692 nm, a slope efficiency of 80 % at an average output power of 60 W could be shown. With the help of simulations we investigate the effect of cross-relaxations on the efficiency and the thermal behavior. We extend our investigations to a rod-type, large-pitch fiber with very large mode area, which is exceptionally suited for high-energy ultrafast operation. Pumping at 1692 nm leads to a slope efficiency of 74 % with a average output power of 67 W, instead of the 38 % slope efficiency obtained when pumping at 793 nm. These results pave the way to highly efficient 2 µm fiber-based CPA systems.
CRIS-Team Scopus Importer:2023-04-20